Glosa do wyroku Naczelnego Sądu Administracyjnego z dnia 12 lipca 2017 r., II FSK 1654/15 (glosa krytyczna) - Halasz, Artur (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2018)
The voting judgment of the Supreme Administrative Court refers to the issue of binding the definition of legal concepts contained in acts outside the tax law system in the process of applying a specific tax act. The author, after analyzing the argumentation indicated by the NSA, formulated critical remarks on the manner of resolving this issue. Therefore, the author's comments on the Supreme Administrative Court judgment illustrate the problem of binding legal definitions from outside the tax law system of specific tax acts in which the concepts are not defined that are difficult for the legal theory and the practice of applying tax law
Keywords: tax law; legal definitions; gloss